2013
DOI: 10.1136/bjsports-2013-092840
|View full text |Cite
|
Sign up to set email alerts
|

Altitude training and haemoglobin mass from the optimised carbon monoxide rebreathing method determined by a meta-analysis

Abstract: ObjectiveTo characterise the time course of changes in haemoglobin mass (Hbmass) in response to altitude exposure.MethodsThis meta-analysis uses raw data from 17 studies that used carbon monoxide rebreathing to determine Hbmass prealtitude, during altitude and postaltitude. Seven studies were classic altitude training, eight were live high train low (LHTL) and two mixed classic and LHTL. Separate linear-mixed models were fitted to the data from the 17 studies and the resultant estimates of the effects of altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
155
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(180 citation statements)
references
References 54 publications
21
155
3
1
Order By: Relevance
“…The decline of ambient oxygen leading to tissue hypoxia, and this extreme physiological stress activates hypoxia-inducible factor 2 (HIF-2) and induces rapid EPO release from kidney (Wang and Semenza, 1996;Wojchowski et al, 2006;Socolovsky, 2007;Yeo et al, 2008;Castrop & Kurtz, 2010;Kapitsinou et al, 2010), indicating that high endogenous EPO level could serve as a stress indicator at altitude. Furthermore, previous studies have demonstrated that circulatory EPO level could markedly increase under physiological stress, such as performing exercise training at altitude of 1500-3000 m (Klausen et al, 1991;Chapman et al, 1998;Wolfarth, 2005;Gore et al, 2013). Similarly, here we also observed that serum EPO concentrations in subjects taking placebo was rapidly elevated and still remained at high levels when subjects returned to sea level after altitude training (*48% above pre-altitude training).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The decline of ambient oxygen leading to tissue hypoxia, and this extreme physiological stress activates hypoxia-inducible factor 2 (HIF-2) and induces rapid EPO release from kidney (Wang and Semenza, 1996;Wojchowski et al, 2006;Socolovsky, 2007;Yeo et al, 2008;Castrop & Kurtz, 2010;Kapitsinou et al, 2010), indicating that high endogenous EPO level could serve as a stress indicator at altitude. Furthermore, previous studies have demonstrated that circulatory EPO level could markedly increase under physiological stress, such as performing exercise training at altitude of 1500-3000 m (Klausen et al, 1991;Chapman et al, 1998;Wolfarth, 2005;Gore et al, 2013). Similarly, here we also observed that serum EPO concentrations in subjects taking placebo was rapidly elevated and still remained at high levels when subjects returned to sea level after altitude training (*48% above pre-altitude training).…”
Section: Discussionsupporting
confidence: 70%
“…It is likely that a mediator other than total RBC number and oxygen consumption had a role in the further prolonged exhaustive run time by RC supplement after altitude training. Another possibility could be that potential effects of RC supplement on oxygen consumption were masked by high altitude exercise training in compared with the findings by Zhang et al (2009) at sea level, because high altitude training per se is an effective factor to markedly promote erythropoiesis and oxygen consumption (Gore et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…With prolonged moderate altitude (2300-3000 m) exposure a progressive increase of approximately 1.1% in tHb-mass for each 100 h of hypoxic exposure over 2 weeks of moderate altitude has been reported in a meta-analysis (Gore et al, 2013), with a proposed ceiling increase across multiple studies of approximately 7% after *500 h (Saunders et al, 2009). The actual measurement of tHb-mass before and following self-supported high-altitude climbing expeditions has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Training sessions completed in hypoxia evoke a higher physiological load than equivalent sessions completed in normoxia. 6 However, the reduced partial pressure of oxygen and subsequent re-duction in oxygen transport and uptake at race-like intensities [7][8][9] affects both performance and perceived exertion.…”
mentioning
confidence: 99%